Responsible innovation in mobility systems: a support for governance of smart and sustainable universities campuses - Souza, Thais Assis de (2022)
There is a global recognition of cities as critical systems to provide sustainable human development. As innovation environments focused on better conditions for collective well-being, cities have been characterized by a high density of population and activities, generating social, educational, cultural and health functions that are developed in a fragile context. This scenario highlights issues related to safety, housing demand, jobs, basic services, infrastructure aspects such as adequate and well-connected transportation systems, and other elements that impact urban life. Mobility, as one of the urban systems, has faced new demands that call attention to the integrity of the natural, economic, and social systems, requiring adequate and integrated planning. For this, it is fundamental to structure a definition of governance that supports the urban practices and processes of regulatory authorities, businesses, and society in a systemic apparatus. Therefore, the aim must be the development of a framework that is more integrative, prospective, responsive, aware of impacts for future generations, and capable of creating, capturing, and assimilating value from the scenario that changes and is increasing in terms of opportunity. In this thesis, to cope with this context, we are proposing discussions based on the concept of smart and sustainable cities and communities, quintuple helix (5H), and responsible innovation (RI). The challenges are proposed to be eased by developing a responsive performance system based on critical success factors (CSFs) analysis. In this sense, the general objective is to identify and discuss critical factors to support the development of a responsible urban mobility system as an element of smart and sustainable cities. In order to address a context of less complexity than cities, this thesis proposes an application on University Campuses. Like cities, university campuses are ecosystems composed of different entities that operate under a more centralized policy and legislative body, such as a smaller scale of a municipal government. In this project, two universities were chosen as cases for study. Both institutions aim to incorporate smartness and sustainability aspects in their campuses and mobility system: Federal University of Lavras (Brazil) and University of Paris-Saclay (France). This application is guided by a Design Science approach and presents a qualitative methodological character with an exploratory nature. Data collection was based on primary and secondary sources: academic literature, official documents, focus groups, and online surveys. Concerning analysis, content analyzes, descriptive qualitative analyzes, descriptive, and multivariate were performed. The qualitative analysis of the case studies will provide a holistic view of mobility systems. The different national contexts will high-light important aspects that can contribute to policy and managerial processes. Furthermore, communities can be supported to structure benchmarks as well as solution finding and decision-making processes appropriately, stimulating relevant and necessary discussions about a responsible urban mobility system. The proposed discussions are guided to highlight contextual insights, being relevant to the macro level of cities and other communities.